A hybrid approach to maximize safety with thoracoscopic Nuss procedure after prior sternotomy - Krista Lai; Dawn E. Jaroszewski; Lisa E. McMahon (Elsevier, 2022)
The Nuss procedure for pectus excavatum repair in patients with history of sternotomies is technically challenging with the potential for serious complications including cardiac injury, which has been reported in 7% of cases. A pre-emptive redo sternotomy to free the mediastinum of adhesions and permit safe, unobstructed bar passage may mitigate this risk. Forced sternal elevation with sternal wires and the Rultract retractor creates additional space to achieve this. We advocate that this hybrid approach be standard of care to minimize intraoperative risks for this cohort of patients.